The Effectiveness of the Administrative Court in Regional Personnel Disputes: A Case Study of the 2025 Selection of the Regional Secretary of Banten Province (Merit System and Chronology of the Dispute) - Mahmud Kusuma; Budi Ilham Maliki; Asep Hidayat; Yayan Kustinah; Chandra Pratiwi; Eko Rudianto (LPPM UNU CIREBON, 2025)
Study purpose. This study aims to analyze the effectiveness of the State Administrative Court (PTUN) in Regional Personnel Disputes, especially in Banten Province, related to the Selection of Regional Secretary of the Banten Provincial Government in 2025. The assessment of the State Administrative Decision (KTUN) in the selection of the Regional Secretary of the Banten Provincial Government in 2025 is intended to be used as an instrument to measure the application of the General Principles of Good Governance or 'AUPB' such as the principle of the ASN merit system, transparency/openness, and independence/impartiality of the Selection Committee. Materials and Methods. This research combines a juridical-normative approach (analysis of the State Administrative Court Law, the Civil Servant Law, the Government Regulations on Civil Servant Management, and the Supreme Court Regulation) and a juridical-empirical approach (tracing the chronology of administrative efforts and lawsuits at the State Administrative Court, as well as documented coverage of the hearings). The theoretical basis uses the theory of legal effectiveness and administrative justice, where effectiveness depends on the substance of norms, enforcement structures, legal culture, and means of execution. Results. The study shows that related to Regional Personnel Disputes, especially in Banten province, specifically related to the Selection of the Regional Secretary of the Banten Provincial Government in 2025, has been appropriately resolved through the procedural legal mechanism in the form of litigation at the relevant PTUN. However, dynamics are still found at the implementation level, including: (i) The case related to the Banten Regional Secretary is registered at the Jakarta PTUN and the trial is recorded as having been postponed because the defendant's answer is not ready (agenda September 23, 2025) and is still ongoing, (ii) the emergence of polemics on the merit system and transparency of the Selection Committee has emerged in local media reports, and (iii) as a precedent, the dispute over the position of Regional Secretary in Banten was also tested at the Serang PTUN in 2022 (case: 15/G/2022/PTUN.SRG related to the dismissal of the Regional Secretary), showing a pattern that strategic personnel issues in Banten repeatedly become the object of TUN disputes. Conclusion. Settlement of regional personnel disputes through legal mechanisms such as litigation at the State Administrative Court (PTUN) remains the formal means of resolving cases. However, several recommendations can be made to strengthen this process, including strengthening transparency standards for the selection of High-Leading Positions (JPT), optimizing the role of the National Civil Service Agency (KASN), and ensuring compliance by the parties in implementing PTUN decisions. The findings are progressive because the 2025 case is still ongoing, so the results section is continuously updated following the official trial agenda.